Ayurvedic Management of Palmoplantar Psoriasis: An Evidence Based Case Report - Saranya P; PM Madhu; Farseena K (International Journal of Ayurveda and Pharma Research, 2025)
Palmoplantar psoriasis is a chronic dermatological condition that primarily affects the palms of the hands and soles of the feet, leading to significant functional disability. It is characterised by hyperkeratosis, scaling, and thickening of the skin. The condition may also involve painful fissures and bleeding. In this case study, an 83-year-old male patient presented to the Inpatient department (IPD) with complaints of blackened, thickened skin lesions, along with cracks, itching, scaling, and pain on both his feet and hands, lasting for the past three months. From the clinical presentation, the condition can be correlated with "Vipadika Kushta" in Ayurveda. The negative impact of palmoplantar psoriasis on the patient’s personal and social life is profound, as it severely hampers daily activities and mobility. While modern medicine mainly focuses on topical treatments, complete recovery is often not achievable. However, with the help of Ayurvedic treatment modalities, the patient experienced significant relief from pain and itching. Additionally, the cracks and discolouration of the skin improved considerably, showcasing the potential benefits of Ayurveda in managing such chronic conditions.